Feasibility and Acceptability of the Informant AD8 for Cognitive Screening in Primary Healthcare: A Pilot Study. (7th December 2014) - Dong, YanHong; Cheng, Tuck Seng; Tsou, Keith Yu Kei; Chan, Qun Lin; Chen, Christopher Li-Hsian
Abstract : Objectives. The utility of informant AD8 for case finding of cognitive impairment at primary healthcare settings is unknown and therefore its feasibility and acceptability for targeted screening at a primary healthcare clinic should be investigated. Methods. The informants of older adult patients attending a primary healthcare clinic in Singapore were administered the AD8. Positive screening findings were provided to patients' primary care physicians for referrals to specialist memory clinics. The acceptability of AD8 was evaluated by collecting feedbacks from the informants and primary care physicians. Results. 205 patients and their informants were recruited. However, 6 (2.9%) informants were uncontactable, while the majority of the remaining 199 patients with completed AD8 (96.5%, n = 192 ) found it acceptable where 59 (29.6%) patients were deemed cognitively impaired (AD8 ≥ 2). Clinicians (100%, n = 5 ) found the AD8 helpful in facilitating referrals to memory clinics. However, most referral recommendations (81.4%, n = 48 ) were declined by patients and/or informant due to limited insight of implications of cognitive impairment. Conclusions. The AD8 can be easily administered and is well tolerated. It detected cognitive impairment in one-third of older adult patients and therefore may be useful for case finding of cognitive impairment in the primary healthcare.